Home Visit To Improve Parents' Understanding Of Children's Multiple Intelligence - Arini Istidama Amalia (Pesantren Reviews, 2023)
This study aims to describe the procedures for implementing the home visit program for parents' understanding of the multiple intelligences of children at RA Ulul Albab Jember. The collection of data used in research is observation, interviews and documentation. Data analysis uses data source triangulation techniques and theory triangulation. Results The procedure for implementing the home visit program for parents' understanding of the multiple intelligences of children at RA Ulul Albab Jember consists of several stages, namely; (1) planning stage. This is done in order to minimize mistakes when carrying out home visits. (2) stages of home visit implementation. This stage is the core stage, namely the implementation of home visits to increase parents' understanding of multiple intelligences. (3) home visit evaluation stage. This stage serves to correct mistakes made during the home visit.